A methodology for evaluating the fracture width of a notched RC multiple-layer flat slab under cyclic loading - Nawir Rasidi; Taufiq Rochman (MethodsX, 2025)
This paper introduces an innovative method for assessing crack width in notched reinforced concrete (RC) slabs under cyclic loads, considering both precast and in-situ layers in composite slab configurations. The study addresses gaps in current research on crack behaviour under fatigue, providing a method that evaluates stress distribution and crack spacing around flexural notches. By employing empirical curvature values and comparing predicted crack widths with experimental data and fracture mechanics standards, this approach accounts effectively for tension stiffening effects.The results reveal that composite slabs exhibit controlled crack propagation and improved resistance under cyclic loading, demonstrating the effectiveness of the composite action. This model not only bridges the gap between theory and practical application in crack width prediction but also contributes to optimizing durability in RC structures exposed to cyclic stresses. The methodology aids in extending structural service life and refining design criteria in fatigue and fracture engineering. • Measures crack width and spacing near flexural cracks using empirical curvature data. • Validates predictions with established standards, demonstrating method accuracy. • Offers a model for crack behaviour that aligns with fatigue and fracture mechanics in RC slabs.